Exploring the Mediating Effect of Job Satisfaction on the Compensation Performance Relationship in a Fast-Moving Consumer Goods Company - Dhyah Harjanti; Fadel Brilliant Sugito; Wilma Laura Sahetapy (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2025)
This study highlights the importance of human resources in maintaining company performance and sustainability. In the context of a Fast-Moving Consumer Goods Company, compensation is viewed as a strategic factor that can improve employee motivation and work results. Job satisfaction is considered a potential link between compensation and employee performance. This study used a quantitative approach with 150 respondents who had worked for at least one year. Data were analyzed using SmartPLS 4.0. The results showed that compensation had a positive and significant effect on job satisfaction, and job satisfaction had a positive effect on employee performance. In addition, compensation was proven to have a significant direct effect on employee performance and also had an indirect effect through job satisfaction as a mediating variable.